Pemanfaatan Permainan Tradisional Dalam Pencapaian Indikator Pembelajaran - Ilham Ilham; Muhammad Ali; Endarman Syaputra; Hendri Munar (Publikasi Pendidikan, 2018)
The objective to be achieved in this activity is to provide an understanding to the penjas teacher of the need to do learning penjas in the form of play for the achievement of learning indicators. Based on the above objective, the target and the expected outcomes are: 1) The penjas teacher can know the various forms of traditional games that can be used for the achievement of learning indicator penjas. 2) The penjas teacher can do the learning of penjas by using traditional games for the achievement of learning indicator penjas. Techniques used in this implementation is to counseling teachers in penjas located in the West Muara Sabak, East Sabak, Geragai and Dendang sub-districts, amounting to approximately 71 people, this activity in cooperation with SMA Negeri 5 and SMA Negeri 8 Tanjung Jabung Timur. The conclusion of the implementation of this devotion are: (1) In an effort to achieve indicators of athletic learning can be done by using traditional game methods. (2) The utilization of traditional games in the achievement of learning indicators has not been done by the teacher of Penjas Orkes in Tanjung Jabung Timur Regency. (3) The used of traditional games in achieving the indicators of learning should be designed accordance with the learning materials.